White collar crime: a comparative perspective - Ligeti, Katalin; Tosza, Stanisław (Hart studies in European criminal law, 2019)
In recent years, criminal justice systems have faced important global challenges in the field of economic and financial crime. The 2008 crisis revealed how strongly financial markets and economies are interconnected and illustrated that misconduct in the economic and financial sectors is often of a systemic nature. The prevention, control and punishment of such crimes is thus confronted with a strong globalisation. Legislators and law enforcers have been searching for adequate responses to combat economic and financial crime by adapting existing policies, norms and practices and by creating new enforcement mechanisms. The aim of this volume is to examine how various national criminal justice systems across Europe deal with the aforementioned challenges. In the first part, it will take a closer look at the following national systems: France, Germany, Poland and Sweden. Furthermore, it will compare the European approach with the American one, as a source of inspiration for unresolved difficulties and future developments. It then goes further to explore those challenging issues regarding the field of economic and financial crime including: the Senior Managers Regime, corporate criminal liability, and whistle-blowers protection. Timely and pertinent, this an important new work on a fast moving field